Virus-encoded cyclin. - Jung, J U (1994)
Herpesvirus saimiri contains an open reading frame called eclf2 with homology to the cellular type D cyclins. We now show that the eclf2 gene product is a novel virus-encoded cyclin (v-cyclin). The protein encoded by the v-cyclin gene of this oncogenic herpesvirus was found to have an apparent molecular size of 29 kDa in transformed cells. v-Cyclin protein was found to be associated with cdk6, a cellular cyclin-dependent kinase known to interact with cellular type D cyclins. cdk6/v-cyclin complexes strongly phosphorylated Rb fusion protein and histone H1 as substrates in vitro. Mutational analyses showed that highly conserved amino acids in the cyclin box of v-cyclin were important for association with cdk6 and for activation of cdk6 kinase activity. Thus, v-cyclin resembles cellular type D cyclins in primary sequence, in its association with cdk6, by its ability to activate protein kinase activity, and by the presence of functional cyclin box sequences. v-Cyclin exhibited a selective preference for association with cdk6 over other cyclin-dependent kinases and a high level of kinase activation. The properties of v-cyclin suggest a likely role in oncogenic transformation by this T-lymphotropic herpesvirus.